MODEL OF HUMAN RESOURCES PERFORMANCE IMPROVEMENT AT PORT OPERATOR UNIT (UPP) CLASS III JEPARA, PATI AND REMBANG THROUGH KNOWLEDGE SHARING, QUALITY OF INFORMATION TECHNOLOGY AND COMMITMENT AS INTERVENING VARIABLE - Sugito Sugito; Nunung Ghoniyah (IJIBE (International Journal of Islamic Business Ethics), 2017)
This study aimed to examine the effect of knowledge sharing and quality of information technology on performance. In addition, this study used commitment as intervening variable to test the correlation between knowledge sharing and quality of information technology on performance. This research was conducted with survey method bydistributing questionnaires to 100 employees of the Port Operator Unit (UPP) Class III Jepara, Pati and Rembang. The Sampling was done by using simple random sampling technique for the Port Operator Unit (UPP) Class III Jepara, Pati and Rembang. Furthermore, the commitment as an intervening variable is able to mediatethe correlation on the effect of knowledge sharing and quality of information technology on performance.Keywords: Knowledge Sharing, Quality Information Technology, Commitment, Performance